Revision of the costata-group of Alona s. lato (Cladocera: Anomopoda: Chydoridae) confirms its generic status - Sinev, Artem Y.; Dumont, Henri J. (European Journal of Taxonomy, 2016)
By taking Flavalona gen. nov. out of Alona s.l. (Cladocera: Anomopoda: Chydoridae), the last major clade has now been removed from this polyphyletic assemblage. Flavalona gen. nov. is a monophylum defined by having three, rarely two connected head pores and slit-shaped, rarely rounded lateral head pores. Postabdomen rather long, distally narrowed, with robust marginal denticles and weakly developed lateral fascicles of setules. End-claw weakly curved and with short basal spine. Male postabdomen with gonopores opening at the end of a penis-like outgrowth. Trunk limbs: exopodite of P2 with seta; inner portion of P4 with flaming-torch shaped setae; P5 with filter plate of three setae; P6 a large simple lobe. The relationship of the new genus with other Aloninae remains to be determined. A key to the 11 species of the genus is provided and a discussion of their geographic distribution and habitat type is given.